INTRODUCTION OF AUGMENTED REALITY AND VIRTUAL REALITY IN THE GROWING EDUCATION SECTOR: A REVIEW - et. al., Saket Badge (International Journal of Modern Agriculture, 2021)
Technology has been growing fast and influencing different aspects of life such as healthcare, entertainment, and many other fields. Education is the base for a flourishing society, and the transfer of knowledge has been a top preference for civilization since the very beginning. The education sector is using technology like smart teaching using video lectures, distance learning, and other technology. Reality technology has capabilities to make good engagement with a learner using advanced graphics and interactive videos. This 3-dimensional world of education is effectively changing the traditional teaching method. These reality technologies use combining the physical and virtual worlds. Using advanced technology anybody can learn anything using the internet, for better engagement augmented and virtual reality will help lots of learners. This article will provide information about the implementation of reality technology in the Ed-tech industry and comparison analysis of different Ed-tech platforms which are currently providing a reality technology..